Targeted metagenomics using next generation sequencing in laboratory diagnosis of culture negative endophthalmitis. Issue 4 (April 2021) - Mishra, Deepanshi; Satpathy, Gita; Chawla, Rohan; Paliwal, Daizy; Panda, Subrat Kumar
Abstract: To study the feasibility of 16S rRNA metagenomics using next generation sequencing (NGS) along with broad range PCR assay for 762 bp region of 16S rRNA gene with Sanger's sequencing, in microbial diagnosis of culture negative endophthalmitis. Vitreous fluid from 16 culture negative and one culture positive endophthalmitis patients, admitted to a tertiary care hospital were processed for targeted metagenomics. NGS of 7 variable regions of 16S rRNA gene was done using Ion Torrent Personal Genome Machine (PGM). Sequence data were analyzed using Ion Reporter software using QIIME and BLSATN tools and Greengenes and NCBI–Genbank databases. Bacterial genome sequences were detected in 15 culture negative and culture positive vitreous specimens. The sequence reads varied between 25, 245–540, 916 with read length between 142bp–228bp and coverage depth was 41.0X and 81.2X. Operational taxonomic unit (OTUs) of multiple bacterial genera and species were detected in 13 culture negative vitreous specimens and OTUs of a single bacterial species were detected in 2 culture negative and 1 culture positive specimens; one negative specimen had no bacterial DNA. Maximum numbers of OTUs detected by NGS for a bacterial species from any vitreous specimen was the one which was detected and identified by Sanger's sequencing in broad range PCR. All the bacteria were belonging to clinically relevant species. Broad range PCR with sequencing failed to identify bacteria from 5 of the 16 (31.25%) culture negative vitreous specimens. Metagenomics could detect and identify bacterial pathogens in 15 of the 16 culture negative vitreous specimen's up to species level. With rapidly decreasing cost, metagenomics has a potential to be used widely in endophthalmitis diagnosis, in which culture negativity is usually high. Abstract : Metagenomics; Next generation sequencing; Endophthalmitis; Operational taxonomic units.